Airport-based photovoltaic applications - Sreenath, Sukumaran; Sudhakar, Kumarasamy; Ahmad Fitri, Yusop (Wiley Online Library, 2020)
Abstract Nowadays, airports' interest in solar photovoltaics (PVs) is increasing. It is a way to lower the burden of energy costs and to show environmental stewardship. This paper aims to study the application of PVs in the airport environment. Solar projects in airport areas across the world were studied to find the techno-economic and environmental aspects of airport-based solar PV application. The favorable factors for solar PV are observed to be effective land utilization, low height profile, versatility, flexibility, and mature silicon PV technology. The major considerations for airport-based solar PV applications were glare occurrence, radar interference, and penetration into airspace. Airport's weather and soil conditions, selection of PV technology, glare impact, site selection, and grid interconnection issues were the technical challenges. It was observed that economic factors such as reduced energy cost, life cycle cost, and sustainability grants and incentives make solar projects in airports attractive. Carbon mitigation and achievement of sustainability goals through solar PV installation emphasized the environmental stewardship of airports. From case studies, it was understood that prior planning, glare assessment, and careful implementation are essential for the success of airport-based solar PV farms. Airport-based solar PV has immense scope in the near future.